Hypogene speleogenesis in dolomite host rock by CO2-rich fluids, Kozak Cave (southern Austria) - Spötl, Christoph; Mangini, Augusto (Geomorphology, 2016)
A growing number of studies suggest that cave formation by deep-seated groundwater (hypogene) is a more common process of subsurface water-rock interaction than previously thought. Fossil hypogene caves are identified by a characteristic suite of morphological features on different spatial scales. In addition, mineral deposits (speleothems) may provide clues about the chemical composition of the paleowater, which range from CO2-rich to sulfuric acid-bearing waters. This is one of the first studies to examine hypogene cave formation in dolomite. Kozak Cave is a fossil cave near the Periadriatic Lineament, an area known for its abundance of CO2-rich springs. The cave displays a number of macro-, meso- and micromorphological elements found also in other hypogene caves hosted in limestone, marble or gypsum, including cupolas, cusps, Laughöhle-type chambers and notches. The existance of cupolas and cusps suggests a thermal gradient capable of sustaining free convection during a first phase of speleogenesis, while triangular cross sections (Laughöhle morphology) indicate subsequent density-driven convection close to the paleowater table. Notches mark the final emergence of the cave due to continued rock uplift and valley incision. Very narrow shafts near the end of the cave may be part of the initial feeder system, but an epigene (vadose) overprint cannot be ruled out. Vadose speleothems indicate that the phreatic phase ended at least about half a million years ago. Drill cores show no evidence of carbon or oxygen isotope alteration of the wall rock. This is in contrast to similar studies in limestone caves, and highlights the need for further wall-rock studies of caves hosted in limestone and dolomite.
Available online 2 December 2015
Im Titel ist die Zahl 2 tiefgestellt
Gesehen am 13.05.2020